The analysis of ecologic-economical aspects and prospects of alternative energy development in Ukraine - Petruk, V. H.; Moroz, O. V.; Kotsiubynska, S. S.; Matsiuk, D. V. (Visnyk of Vinnytsia Politechnical Institute, 2010)
Ecological and economic aspects and prospects of development of alternative energy in Ukraine are considered. Expedience, recoupment and efficiency of introduction of renewable energy sources, in the national economy are investigated.